Steamed Panax notoginseng Attenuates Anemia in Mice With Blood Deficiency Syndrome via Regulating Hematopoietic Factors and JAK-STAT Pathway - Zhang, Zejun; Zhang, Yiming; Gao, Min; Cui, Xiuming; Yang, Yang; van Duijn, Bert; Wang, Mei; Hu, Yupiao; Wang, Chengxiao; Xiong, Yin (Frontiers in Pharmacology, 2020)
Panax notoginseng (Burk.) F. H. Chen is a medicinal herb used to treat blood disorders since ancient times, of which the steamed form exhibits the anti-anemia effect and acts with a “blood-tonifying” function according to traditional use. The present study aimed to investigate the anti-anemia effect and underlying mechanism of steamed Panax notogensing (SPN) on mice with blood deficiency syndrome (BDS) induced by chemotherapy. BDS was induced in mice by cyclophosphamide and acetylphenylhydrazine. A number of peripheral blood cells and organs (liver, kidney and spleen) coefficients were measured. The mRNA expression of hematopoietic function-related cytokines in the bone marrow of mice was detected by RT-qPCR. The janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling pathway was screened based on our previous analysis by network pharmacology. The expression of related proteins and cell cycle factors predicted in the pathway was determined by Western blot and RT-qPCR. SPN could significantly increase the numbers of peripheral blood cells and reverse the enlargement of spleen in a dose-dependent manner. The quantities of related hematopoietic factors in bone marrow were also increased significantly after SPN administration. SPN was involved in the cell cycle reaction and activation of immune cells through the JAK-STAT pathway, which could promote the hematopoiesis.